2020
DOI: 10.1186/s12955-020-1277-8
|View full text |Cite
|
Sign up to set email alerts
|

The quality of life of the patients with diabetes type 2 using EQ-5D-5 L in Birjand

Abstract: Background: Due to high prevalence of diabetes and its complications, evaluating of the patients' quality of life is critical. EQ-5D-5 L is a valid tool for assessing the quality of life in chronic diseases including diabetes. The present study conducted to illustrate the quality of life for the patients who referred to the Diabetes clinic and determine its relationship with their demographic and clinical characteristics in Birjand in 2017. Methods: In this cross-sectional study, 300 patients with type 2 diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
64
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 32 publications
24
64
2
6
Order By: Relevance
“…In addition, the mean EQ-5D-5L index for diabetes patients in this study was lower than human immunodeficiency virus (HIV; 0.80) 32 but higher skin diseases (0.73), 33 respiratory diseases (0.66), 34 dengue fever (0.66), 35 frail elderly (0.58), 36 and elderly after fall injury (0.46). 37 While the mean and median obtained from our study are not consistent with those of Abedini et al, 11 who found 0.89 for EQ-5D-5L and 65.22 for VAS in Iran, Abedini et al's study is the only study that addressed the HRQoL by using the UK EQ-5D-5L value set based on local data in Birjand region, Iran. Part of this higher HRQoL may be due to difference in value sets used to calculate the EQ-5D-5L in two studies.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…In addition, the mean EQ-5D-5L index for diabetes patients in this study was lower than human immunodeficiency virus (HIV; 0.80) 32 but higher skin diseases (0.73), 33 respiratory diseases (0.66), 34 dengue fever (0.66), 35 frail elderly (0.58), 36 and elderly after fall injury (0.46). 37 While the mean and median obtained from our study are not consistent with those of Abedini et al, 11 who found 0.89 for EQ-5D-5L and 65.22 for VAS in Iran, Abedini et al's study is the only study that addressed the HRQoL by using the UK EQ-5D-5L value set based on local data in Birjand region, Iran. Part of this higher HRQoL may be due to difference in value sets used to calculate the EQ-5D-5L in two studies.…”
Section: Discussioncontrasting
confidence: 96%
“…The mean VAS scores were higher in employed subjects. This finding is consistent with that of the recent studies evaluating HRQoL of diabetic patients in Iran 11,14 and Palestine. 45 This could be due to the fact that employed patients in developing countries have more opportunities to have a better socioeconomic status.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations